A New Simulation Framework for Soil–Root Interaction, Evaporation, Root Growth, and Solute Transport. Issue 1 (23rd August 2018) - Koch, Timo; Heck, Katharina; Schröder, Natalie; Class, Holger; Helmig, Rainer
Abstract : Core Ideas: We present a locally mass‐conservative flow, transport, and root–soil interaction model. We include a sustainable, flexible research software framework for plant‐scale model development. This is an improved model concept for fluid dynamic processes, evaporation, root water uptake. We have developed a general model concept and a flexible software framework for the description of plant‐scale soil–root interaction processes including the essential fluid mechanical processes in the vadose zone. The model was developed in the framework of non‐isothermal, multiphase, multicomponent flow and transport in porous media. The software is an extension of the open‐source porous media flow and transport simulator DuMu x to embedded mixed‐dimensional coupled schemes. Our coupling concept allows us to describe all processes in a strongly coupled form and adapt the complexity of the governing equations in favor of either accuracy or computational efficiency. We have developed the necessary numerical tools to solve the strongly coupled nonlinear partial differential equation systems that arise with a locally mass conservative numerical scheme even in the context of evolving root architectures. We demonstrate the model concept and its features, discussing a virtual hydraulic lift experiment including evaporation, root tracer uptake on a locally refined grid, the simultaneous simulation of root growth and root water uptake, and an irrigation scenario comparing different models for flow in unsaturated soil. We have analyzed the impact of evaporation from soil on the soil water distribution around a single plant's root system. Moreover, we have shown that locally refined grids around the root system increase computational efficiency while maintaining accuracy. Finally, we demonstrate that the assumptions behind the Richards equation may be violated under certain conditions.